Drivers of Economic Outcomes for Single Women without Children in Retirement - Hamilton, Myra; Hodgson, Helen; Bradbury, Bruce (Thomson Reuters, 2022)
Women, especially single women, are much more likely than men to live in poverty in old age and have lower median superannuation balances than men. This is generally attributed to interrupted workforce participation and the gender pay gap. This article examines the effects of Australian policy settings on a subgroup of older single women: older single women without children. Little is known about this group, including to what extent gender inequalities persist when the motherhood penalty is removed. The study included: a review of relevant legislation; an analysis of Australia’s Housing and Labour Dynamics in Australia (HILDA) Survey; qualitative research with an online community of 45 older single women and interviews with 10 financial services providers. Findings suggest that higher earning capacity did not translate into better financial security in old age, as being single resulted in lower household wealth, including home ownership. This group also experiences career interruptions associated with family care. This led to insecurity in later life.